Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173952
|View full text |Cite
|
Sign up to set email alerts
|

I Really did That

Abstract: Input on the skin is emerging as an interaction style. At CHI 2012, Coyle and colleagues identified an increase in the sense of agency (SoA) as one benefit of skin input. However, their study only compared skin input to button presses and has not, to our knowledge, been replicated. Therefore, we had 24 participants compare skin input to both button presses and touchpad input, measuring SoA using the Libet Clock paradigm. We replicate previous findings regarding increased SoA in skin versus button input and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…For example, how does one design a technology that truly provides the experience of "I did that" rather than "The tool did that for me"? Intentional binding provides us with a tool from neuroscience for evaluating these phenomenas quantitatively [14,9]. However, we find that the design space is not yet well understood as more and more interfaces find new configurations for shared agency [34].…”
Section: Designing For Variable Agencymentioning
confidence: 88%
“…For example, how does one design a technology that truly provides the experience of "I did that" rather than "The tool did that for me"? Intentional binding provides us with a tool from neuroscience for evaluating these phenomenas quantitatively [14,9]. However, we find that the design space is not yet well understood as more and more interfaces find new configurations for shared agency [34].…”
Section: Designing For Variable Agencymentioning
confidence: 88%
“…Since the IB paradigm has been widely employed in the literature; demonstrated to be a viable metric to implicitly assess the SoA [67], and it has been recently employed in HCI to measure agency for different input commands and system feedback [11,21,24], we employed this method for our study.…”
Section: The Sense Of Agencymentioning
confidence: 99%
“…A recent study has shown that if a system does not support agency, the user might feel discouraged from using it [61]. Within human-computer interaction (HCI) research, it has been shown that on-skin input [45] produces higher SoA than keyboard and touchpad inputs [11,24], and that auditory and haptic feedback elicit higher SoA than visual feedback only [21]. However, the role of smell on agency remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Wagner et al [64] introduced a body-centric design space to describe, classify and compare different multisurface interaction techniques. Prior work reported on the various input modalities and user preferences for on-skin input [73], identified user strategies for creating on-body gestures [51] and revealed that on-skin input increased the sense of agency [5].…”
Section: Related Workmentioning
confidence: 99%